Numerical investigation of the effect of three-dimensional modified parallel flow field designs on proton exchange membrane fuel cell performance. (18th May 2020) - Lim, B.H.; Majlan, E.H.; Daud, W.R.W.; Rosli, M.I.; Husaini, T.
Highlights: The effect of modified parallel flow field patterns on PEMFC performance was investigated. The impact of operating temperature on performance was investigated. The impact of air stoichiometry on performance was investigated. Abstract: Uneven flow resistance can cause a cell to have uneven distributions of temperature and current density. In this study, a three-dimensional (3-D) model with modified parallel flow field patterns is constructed, and simulation is performed to study the reactant distribution and cell performance. Two different modified parallel flow fields are applied to the cathode and anode. The flow characteristics and current density, temperature, and water distributions are analyzed with computational fluid dynamics (CFD). The results indicate that the hydrogen and air reactants are uniformly distributed in a gas diffusion layer (GDL) and gradually decrease from the inlet to the outlet for all channels. The numerical results show that modified parallel flow fields provide evenly distributed current density generation, where the reactant is uniformly distributed in the flow field. This property reduced the likelihood of forming hot spots and consequently enhanced the PEMFC performance.